Prevalence of oral and oropharyngeal human papillomavirus infection in Brazilian population studies: a systematic review - Matos,Leandro Luongo de (2015)
ABSTRACT INTRODUCTION: Human papillomavirus has been associated with head and neck squamous cell carcinoma. However, there is no conclusive evidence on the prevalence of oral or pharyngeal infection by human papillomavirus in the Brazilian population. OBJECTIVE: To determine the rate of human papillomavirus infection in the Brazilian population. METHODS: Systematic review of published articles. Medline, The Cochrane Library, Embase, Lilacs (Latin American and Caribbean Health Sciences) and Scielo electronic databases were searched. The search included published articles up to December 2014 in Portuguese, Spanish and English. A wide search strategy was employed in order to avoid publication biases and to assess studies dealing only with oral and/or oropharyngeal human papillomavirus infections in the Brazilian population. RESULTS: The 42 selected articles enrolled 4066 patients. It was observed that oral or oropharyngeal human papillomavirus infections were identified in 738 patients (18.2%; IC 95 17.6-18.8), varying between 0.0% and 91.9%. The prevalences of oral or oropharyngeal human papillomavirus infections were respectively 6.2%, 44.6%, 44.4%, 27.4%, 38.5% and 11.9% for healthy people, those with benign oral lesions, pre-malignant lesions, oral or oropharyngeal squamous cell carcinoma, risk groups (patients with genital human papillomavirus lesions or infected partners) and immunocompromised patients. The risk of human papillomavirus infection was estimated for each subgroup and it was evident that, when compared to the healthy population, the risk of human papillomavirus infection was approximately 1.5-9.0 times higher, especially in patients with an immunodeficiency, oral lesions and squamous cell carcinoma. The rates of the most well-known oncogenic types (human papillomavirus 16 and/or 18) also show this increased risk. CONCLUSIONS: Globally, the Brazilian healthy population has a very low oral human papillomavirus infection rate. Other groups, such as at-risk patients or their partners, immunocompromised patients, people with oral lesions and patients with oral cavity or oropharyngeal squamous cell carcinoma have a high risk of human papillomavirus infection.